PERAN EVALUASI PEMBELAJARAN PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM KELAS 12 DI SMK NEGERI 1 KARANGANYAR - Rani Tri Damayanti; Aisyah Nur Kholifatun Jannah; Anisa Fadilah Hidayati (Journal of Student Research, 2024)
The purpose of this research is to determine the important role of learning evaluation in the learning process at SMK Negeri 1 Karanganyar. Assessment is a very important part of learning and teaching. If learning is important to foster students' spiritual development, then assessment needs to function as an informant to assess the success of learning. Without evaluation activities, it is impossible to find information about the pros and cons of the teaching activities carried out. In some rules, ethics and behavior cannot be ignored in evaluation. Therefore, it is very important to carry out an evaluation of the learning itself. This research approach is descriptive qualitative in which the informant is an Islamic Religious Education teacher who teaches at SMK Negeri 1 Karanganyar. He was chosen by the researcher because he felt he was experienced and had the criteria to answer the questions given by the researcher. An in-depth semi-structured one-on-one interview was conducted to examine his views regarding the important role of learning evaluation in the learning process at SMK Negeri 1 Karanganyar. This research found that in the evaluation stage at SMK Negeri 1 Karanganyar, the evaluation process activities at this school were carried out well. This is very useful for teachers and students, this can be seen from the evaluation process which consists of affective, cognitive and psychomotor assessments.